32 INTRAVITAL IMAGING DEMONSTRATES INCREASED GLOMERULAR PROTEIN PERMEABILITY PRECEDING PROTEINURIA IN PUROMYCIN AMINONUCLEOSIDE NEPHROSIS. (1st March 2005) - McCarthy, E. T.; Sharma, R.; Reddy, S. R.; Sandoval, R. M.; Dunn, K. W.; Molitoris, B. A.; Savin, V. J.; Sharma, M.
Abstract : Glomerular and tubular events that occur early in the course of proteinuric disease are incompletely understood. To determine the onset of altered glomerular protein permeability, we studied Munich-Wistar rats after a single injection of puromycin aminonucleoside (PAN, 100 mg/kg i.p.) or saline. We isolated glomeruli from rats 1, 2 or 3 hrs after PAN, and measured albumin permeability (Palb) using relative change of glomerular volume to an oncotic gradient. Next, we used intravital two-photon microscopy to study rats 3, 5 or 7 days after PAN. Immediately prior to microscopy, rats were injected with Cascade Blue dextran (MW 3, 000), Rhodamine albumin (red; MW 66, 000) and Oregon Green human apo-transferrin (MW 80, 000). Images were obtained before and every 1-2 min up to 1 hr after injection with labeled markers. Urinary protein excretion was measured 1, 3 or 5 days after PAN. Palb of isolated glomeruli was increased as early as 1 hr after PAN (0.46 ± 0.17 vs control 0.002 ± 0.09, p<0.05; n = 5 glom in each group), and was maximally increased at 3 hr (0.80 ± 0.11, p<0.001 vs control). Two-photon microscopy showed increased glomerular macromolecular filtration as evidenced by greater fluorescence in tubular cells and lumina by 3 days after PAN, prior to the onset of increased urinary protein excretion. Evidence of tubular reabsorption of proteins, i.e. red, green or white (combination of 3 markers) endosomes, and luminal protein became increasingly evident 5 and 7 days after injection. Urinary protein excretion was not significantly increased compared to control until 5 days after PAN (340.0 vs 51.4 mg/d). We conclude that glomerular protein permeability increases prior to onset of proteinuria in PAN injury, and that two-photon microscopy and Palb assay are powerful tools to study glomerular and tubular events in proteinuric disease. Our findings strongly support our hypothesis that glomerular permeability increases prior to proteinuria in models of glomerular injury, and that proteinuria occurs only after tubular reabsorptive capacity is exceeded.